Hepatobiliary Scintigraphy in Cholecystocolonic Fistula. (August 2020) - Philip, Justin T.; Noor, Muhammad; Leyva, Alexander; Contreras, Francisco
Abstract : Abstract: We report a case of a 50-year-old man diagnosed with cholecystocolonic fistula (CCF), confirmed by scintigraphy. After negative initial radiologic workup, a colonoscopy revealed findings of right-sided ischemic colitis. Soon after, a febrile episode prompted a repeat abdominal CT scan demonstrating a possible CCF, later confirmed with a nuclear medicine hepatobiliary scintigraphy and treated surgically. Less than 10% of CCFs are diagnosed preoperatively.